Can i trust you? incorporating supplier trustworthiness into supplier selection criteria. Issue 8 (3rd August 2022) - Prior, Daniel D; Saberi, Morteza; Janjua, Naeem Khalid; Jie, Ferry
ABSTRACT: Supplier selection criteria normally reflect elements of the supplier's value proposition or the supplier firm itself. These elements ultimately represent a supplier firm's promise to the buyer firm. While a plethora of decision-making models exist, none focus on the most important question of all: 'can I trust you?'. This paper begins with a structured literature review to develop an encompassing taxonomy of supplier selection criteria. The structured literature review supports the claim that supplier trustworthiness is only an implicit consideration in supplier selection criteria. Therefore, the study develops a new conceptual framework to capture supplier trustworthiness as a selection criterion.